PENGARUH RETURN ON ASSETS DAN RETURN ON EQUITY TERHADAP RETURN SAHAM SYARIAH PADA PERUSAHAAN CONSUMER GOODS (FOOD AND BEVERAGES) YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX PERIODE 2018-2020 - Irmawati Irmawati; Rahmat Ilyas; Mandala Faldini (Budgeting: Jurnal Akuntansi Syariah, 2022)
In investing, investors are faced with uncertainty between the returns to be obtained and the risks they will face. For this reason, investors need financial information that is used as an important indicator to assess the company's performance and stock returns on the investments they make. Financial reports, especially those related to return on assets and return on equity, are one of the important information used by investors to assess company performance. This study aims to determine the effect of return on assets and return on equity on sharia stock returns in Consumer Goods companies listed on the Jakarta Islamic Index for the 2018-2020 period. The type of this research is descriptive quantitative with secondary data type. This research was conducted on Consumer Goods companies listed on the Jakarta Islamic Index for the 2018-2020 period. The sampling technique used purposive sampling with data analysis techniques using panel data analysis techniques and consisted of population and data samples, design, research models, data instruments and multiple regression tests. Data collection techniques consist of literature studies, previous research and data obtained from quarterly financial reports published on Consumer Goods companies listed on the Jakarta Islamic Index. The population used are companies in the Jakarta Islamic Index index on the Indonesia Stock Exchange, with a sample of 4 issuers where there are 48 data taken for 3 years from 2018-2020. The results of this study indicate that partially return on assets (ROA) has a positive and significant effect on Islamic stock returns with the acquisition of a probability value of 0.02130 <0.05 and return on equity (ROE) has a negative and significant effect on Islamic stock returns with the acquisition of probability values. of 0.0140 < 0.05. While the return on assets (ROA) and return on equity (ROE) variables together show a significant effect on sharia stock returns.